2020
DOI: 10.1016/j.omtn.2019.11.031
|View full text |Cite
|
Sign up to set email alerts
|

MSC-Secreted Exosomal H19 Promotes Trophoblast Cell Invasion and Migration by Downregulating let-7b and Upregulating FOXO1

Abstract: Exosomes perform important functions for intercellular communication through extracellular signaling pathways, leading to the regulation of important biological processes, including cell proliferation, but also systemic dysfunctions such as preeclampsia (PE). However, the inhibitory effects of mesenchymal stem cell (MSCs)-derived exosomes in PE remain largely unknown. Thus, we assessed the possibility that exosomes could transport long non-coding RNA H19 and the correlation between H19 and the apoptosis of tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…Indeed, H19 can act not only as an intrinsic factor, but can also act on neighboring cells. For instance, the involvement of the exosomes-derived expression of H19 has been demonstrated in specific phenomena and pathologies such as trophoblast cell invasion, diabetic foot ulcers, and chronic cholestatic liver diseases, supporting our idea that exosomal H19 can extend its action to surrounding cells [96][97][98]. In cancer models, it has been demonstrated that H19 expression is upregulated in non-small cells lung cancer, particularly in gefitinib-resistant cells.…”
Section: H19 Expression Is Propagated In the Tumor Micro-environment supporting
confidence: 62%
“…Indeed, H19 can act not only as an intrinsic factor, but can also act on neighboring cells. For instance, the involvement of the exosomes-derived expression of H19 has been demonstrated in specific phenomena and pathologies such as trophoblast cell invasion, diabetic foot ulcers, and chronic cholestatic liver diseases, supporting our idea that exosomal H19 can extend its action to surrounding cells [96][97][98]. In cancer models, it has been demonstrated that H19 expression is upregulated in non-small cells lung cancer, particularly in gefitinib-resistant cells.…”
Section: H19 Expression Is Propagated In the Tumor Micro-environment supporting
confidence: 62%
“…MSC-originated exosomes overexpressing H19 reduced let-7b and strengthened forkhead box protein O1 (FOXO1) expression to trigger the protein kinase B (AKT) pathway, thus enhancing trophoblast activities. 8 A report summarized the exo-miRNA of umbilical cord blood in healthy and PE pregnant females systematically and validated that miR-125a-5p dysregulation might influence HTR8/SVneo cell angiogenesis, which is an indicative of miR-125a-5p involvement throughout PE progression. 10 Placenta-connected serum exosomes could constrain expression of endothelial nitric oxide synthase during PE progression in endothelial cells, and this occurrence may be fairly caused by raised miR-155 expression in the exosomes.…”
Section: Ameliorative Effect Of Exosomes On Pe Ratsmentioning
confidence: 95%
“…The expression of miR-139-3p in rat placental tissues was significantly restored and the expression of PETN and MMP-2 was significantly reduced which causes disfavored uterine placental perfusion. 8 MiRNA were found to interact with mRNA and signaling pathways to regulate biological processes of PE. 22,23 Our study searched the function of hucMSCsecreted exosomal miR-139-5p as well as the downstream PTEN and ERK/MMP-2 pathway in trophoblasts.…”
Section: Ameliorative Effect Of Exosomes On Pe Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Yu, S. et al performed extracellular vesicle long RNA-seq (including lncRNA) on plasma samples collected from 501 subjects, and developed 8 long RNAs for the detection of pancreatic cancer ( 49 ). In addition, there are also studies based on star lncRNAs such as HOTAIR and H19 to explore their roles with exosomes in TME ( 50 , 51 ). Nowadays, a series of exosome databases that collect various public exosome sequencing data are constructed.…”
Section: Exosomal Long Non-coding Rna: Sequencing and Databasementioning
confidence: 99%